Apresentação - França, Alexsandra; Silva, Bruno Duarte Guimarães; Morais, Bruno Vinícius Leite de; Duarte, Denise Aparecida Souza; Baião, Fábio; Malacco, Felipe Silveira de Oliveira; Gonçalves, Gislaine; Parreira, Luiza Rabelo; Nascimento, Maíra; Gorga, Pamela Naumann; Andrade, Paulo Renato Silva de; Marques, Raquel; et al. (Temporalidades, 2016)
Apresentação e editorial para a Quarta Edição do EPHIS.Conselho Editorial da Temporalidades - 2015